Eccentric-Only Versus Concentric-Only Isokinetic Strength Training Effects on Maximal Voluntary Eccentric, Concentric and Isometric Contraction Strength: A Systematic Review and Meta-analysis - Darjan Spudić; Kazunori Nosaka (Sports Medicine - Open)
Abstract Background Conflicting results have been reported regarding the effects of resistance exercise training with eccentric (lengthening muscle) versus concentric (shortening muscle) contractions on changes in maximal voluntary contraction (MVC) strength assessed by different contraction modes. Objective The main objective of this systematic review with meta-analyses was to compare the effectiveness of maximal isokinetic eccentric-only and concentric-only strength training for changes in maximal voluntary eccentric (MVCECC), concentric (MVCCON), and isometric contraction (MVCISO) strength in healthy adults. Methods We conducted a systematic search in PubMed, SPORTDiscus, and Google Scholar from February to March 2024 for studies that met the following criteria: (1) randomized controlled trials; (2) inclusion of eccentric-only and concentric-only strength training groups; (3) use of an isokinetic dynamometer for training and testing; (4) reporting changes over time in MVCCON and MVCECC; and (5) using healthy adult participants. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation approach. A multilevel random-effects model meta‑analyses with robust variance estimation were performed in Rstudio software using metafor and clubSandwich packages. Moreover, sensitivity analysis was performed, excluding the highly influential studies. The potential moderating role of sex, training status and age of the participants, muscles, velocity in training and testing, initial MVCECC, MVCCON, and MVCECC/MVCCON ratio, and training-related variables such as number of repetitions per set, number of sets, rest period between sets, number of sessions per week, and duration of the training protocol were also assessed. Results Twenty-seven studies matched with the criteria, and overall 162 study results were identified and included in the meta-analyses. Greater effects on MVCECC were found after eccentric-only than concentric-only training (Hedges’ g: 1.51; 27 vs. 10%; p < 0.001). However, no differences were evident between the training modalities for changes in MVCCON (Hedges’ g: –0.10; 13% vs. 14%, p = 0.726) and MVCISO (Hedges’ g: –0.04; 18 vs. 17%; p = 0.923). The subgroup analyses showed smaller effect of eccentric-only than concentric-only training on MVCCON when eccentric-only training was performed at higher velocities than the velocities of MVCCON testing (Hedges’ g: –0.99; p = 0.010). Meta-regressions showed that the longer the training period, the greater the superior effect of eccentric-only over concentric-only training on MVCECC. Conclusions Eccentric-only strength training is more effective for improving MVCECC, but both concentric-only and eccentric-only training provide similar effects on improving MVCCON and MVCISO. Further studies are necessary to investigate the mechanisms underpinning the superior effect of eccentric-only training.